CHEMICAL AND NUTRITIONAL COMPOSITION OF RICE DISTILLER DRIED GRAIN WITH SOLUBLES FOR LIVESTOCK AND POULTRY - Naresh Kurechiya; Barun Roy; Guru Prasad Mandal; Bikas Ch. Debnath; Kavita Rawat (Exploratory Animal and Medical Research)
A research study was carried out to assess the gross energy, nutrient composition, fiber fraction, macro- and micro-mineral status, amino acid, and fatty acid profile of Rice Distiller Dried Grain with Solubles (rDDGS), a by-product of the ethanol manufacturing process. Sixteen (16) samples were procured from various manufacturing batches of the ethanol industry. There was a higher gross energy (GE) of 4104.75 kcal/kg than in the original grains. Total ash (TA), nitrogen-free extract (NFE), ether extract (EE), crude protein (CP), crude fiber (CF), dry matter (DM), and acid insoluble ash (AIA) had respective mean values of 90.87, 40.24, 6.26, 7.67, 31.53, 5.15, and 1.45%, respectively. The percentages of neutral detergent fiber (NDF) and acid detergent fiber (ADF) were 37.84% and 14.33%, respectively. The percentages of phosphorus and calcium were 1.20 and 0.57%, respectively. Similarly, trace minerals like iron, copper, zinc, cobalt, and manganese were found to be 67, 14, 34, 16, and 68 ppm, respectively. The glutamic acid (6.65), leucine (3.34), and aspartic acid (6.34) were the most abundant amino acids found in rDDGS, while cystine (0.88) and tryptophan (0.41) were the amino acids with the lowest values, respectively. The rDDGS fat has a high amount of linoleic acid (omega-6) with a value of 36.41% and 37.4% of oleic acid. The samples presented a value of 19.68% of palmitic acid, being the highest among saturated fatty acids.